EVALUASI RANAH SIKAP BERBAHASA TERHADAP PEMAHAMAN LITERASI SISWA SEKOLAH DASAR PADA CERITA RAKYAT “BATU MENANGIS” - Firdaus, Ahmad; Mabruroh, Mabruroh; Shofia Zahra Agustina; Yuyu Yuhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study focuses on the analysis of literacy understanding in folklore. Folk poetry is a part of oral literature that is widely found around the student environment. In the cognitive development of students, folklore is one of the teaching materials that can increase students' understanding of the surrounding area. Thus, it can be analyzed simultaneously related to the evaluation of the realm of students' language attitudes towards literacy understanding from the folklore read. This study is quantitative research with a descriptive research design. The researcher described the students' language attitude towards literacy understanding from the folklore